Typologies and aproaches to the study of Latin American political parties - Barros, Hélio G. de (Revista de Ciências Sociais, 2020)
This bibliographical essay represents an effort to analyse how North American scholars are studying Latin American political parties. The author undertakes an in-depth review of the literature and assesses the different approaches used by North American political scientists in the study of parties, concluding with an extensive bibliography on the subject.